The explanatory theories of the Agrarian Structures of Canary Islands - Miguel Suárez Bosa, Alejandro González Morales (Africana Studia, 2020)
Different explanatory theories about the Canary Archipelago agrarian structures have been developed during the 20th century. In some cases descriptive aspects have predominated, making up a theory concerning the different cultivations that have been taking place along time, from the moment of the conquest, by the Normans and Castilians in the 15th century up to present time. In this way a series of cultures of exportation have taken place like sugar cane, the vineyard, the woodlouse (grana-cochineal) and the barrilla, the cultivations of banana and tomato of nowadays. This theory neither values the production for the internal supply and self-consumption, nor bears the social structure in mind. The main defenders of this theory were the historians Morales Padrón and Morales Lezcano. Later on, other authors (E. Burriel and Álvarez Alonso) introduced the explanations of dualistic type, that is to say, wealthy realities opposite to poor agrarian structures, as if they were different things and without complementarily. Finally, there are explanations of J.S. Sanz and F. Martín Ruíz, where they talk about the different forms of production that take place and reproduce in the Canary Social Formation, doing it from a global point of view. In this paper we try to outline and analyze their theories, at the same time that we contribute our vision f the agrarian structure of the Canaries perhaps we could add something like it come from an analysis of the Canary Social Formation, where economic aspects as social, cultural, geographical and historic aspects of the Archipelago are contemplated. Keywords: Agrarian structures, Canary Social Formation, forms of production.